Assistance Influence on Labor Pain Level - JM Seno Adjie; Ruth WR Putri (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To assess assistance influence on labor pain level. Method: This study was a randomized-clinical, unmasked trial with concealment by measuring labor pain level in two patients group: with and without assistance during labor; each group consisted of 36 subjects. Pain intensity were measured using Faces Pain Rating Scale. Mann-Whitney analysis was done to assess significance of pain level between two groups. Result: Majority of patient who were in non-assisted group had very painful score 50% with mean of VAS 7.38Â±2.12, meanwhile most of assisted group complained painful score 44.44%, with mean of VAS 6.11Â±1.90. Conclusion: There was significance level of painful score between non-assisted and assisted subjects x(p